Evaluation of Efficacy of Serum Adenosine Deaminase Values for Detection of Pulmonary and Extra Pulmonary Tuberculosis - Pandey, Parishrut Prasad; Jaiswal, Vedhant; Sharma, Tara Nath; Vaidhya, Shreeju; Karki, Adhyashree; Dahal, Bibesh; Pradhan, Manohar (Journal of College of Medical Sciences-Nepal, 2024)
Background Tuberculosis is one of the leading cause of morbidity and mortality worldwide and in Nepal. Despite advances in its diagnosis, majority of the cases still go undetected. These account for sputum smear negative and extra pulmonary cases where demonstration of the microorganism is challenging. ADA an enzyme found in all mammalian species is found raised in various effusion body fluids of organs affected by the disease. Time tested studies have also shown that serum values of ADA are elevated in patients affected with the disease thus can aid as supportive evidence in doubtful cases. Methods An Analytical cross sectional Hospital Based study involving 110 with 75 cases and 35 healthy participants was conducted in College of Medical Sciences for 5 months from January to June 2024. Serum ADA levels were measured in all participants, diseased and healthy and collected data was analyzed for significance. Results The mean Serum ADA level in TB patients was found to be 47.01 and that of healthy participants was 14.68. Significant difference in the mean serum ADA level between TB and non TB patients (p-value < 0.001) was found concluding that TB patients have high serum ADA level. Comparisons between mean serum ADA levels in Different types of TB found no significant difference among them with all p- values in each pair being more than 0.5 suggesting that serum ADA levels rise in all forms of TB. Conclusions Serum ADA values are raised in all forms of tuberculosis and can serve as a supportive evidence in patients with Smear negative and Extrpulonary TB where microorganisms is difficult to demonstrate. However further validation need to be done by more studies in the future.